Ijtihad Jamaie (Collective Ijtihad) In Islamic Banking and Finance: A Critical Evaluation on its Position in the Malaysian Legal System - Mohd Lotpi, Mohd Yusob; Farhanin, Abdullah Asuhaimi (2014)
The new innovations in Islamic banking and finance show that this industry is developing and growing rapidly. These new innovations can also be regarded as a reflection of the flexibility of Islamic law. This current phenomenon obliquely rejects the theory of Joseph Schacht asserting that Islamic law is obsolete to modern life as it is inflexible and not accommodative to the modern constant changes. Besides, what is imperative to be observed is the whole innovation as mentioned above culminated due to the application of ijtihad especially ijtihad jamaie (collective ijtihad). In Malaysia, this collective ijtihad plays a big role in this industry thanks to the law regulated by the government (legislative body) which vests certain power to the Shariah Advisory Council to do this kind of ijtihad. This paper will examine the concept of collective ijtihad and how (within legal framework) it is applied in the Islamic banking and finance industry in Malaysia.